Harmonisasi Hukum Adat dan Hukum Positif dalam Penanganan Kasus Kawin Tangkap Sebagai Tindak Pidana Kekerasan Seksual - Az-zahra, Ratu Fatimah; Yesenia, Carissa; Maharani, Diah Puspita; Vierly, Azahra; Solihah, Zahrotu; Juliarti, Putri; Wardah, Syahla Ardhelia Ayu (Primagraha Law Review, 2025)
The phenomenon of the Capture Marriage Tradition (Piti Rambang) in Sumba is a crime against humanity involving forced marriage and sexual violence, resulting in victims losing their constitutional rights. This is contrary to the Marriage Law, Human Rights, and the 1945 Constitution. This customary marriage was originally a good tradition but now shows a mismatch between positive law and tradition. This issue needs to be studied because arranged marriages violate human rights and have a negative impact on women's psychology. This case reflects gender inequality. This research aims to find out the challenges in legal protection of victims of catch marriage in the Indonesian legal system and efforts to harmonize customary law and positive law in handling this case as a crime of sexual violence. The method used is Normative Juridical, with a qualitative and descriptive approach to analyze social phenomena that erode social standards, laws, and beliefs. Indonesian legal regulations on marriage, particularly capture marriage, became the main source of data. The results of the study show that catch marriage has now deviated from its original tradition, with elements of physical, psychological and sexual violence. Challenges to legal protection include the absence of specific regulations, low public awareness, patriarchal dominance, and conflicts between customary and national laws. This research offers a harmonization strategy through socialization, collaboration between traditional leaders and the government, the formation of local regulations, and strengthening the role of legal apparatus to protect women's rights in the Indonesian legal system.